2008
DOI: 10.1021/ma800816j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Symmetry of Molecular Weight Distribution in Block Copolymers on Formation of “Metastable” Morphologies

Abstract: Polystyrene-b-poly(methyl acrylate) (PS−PMA) copolymers were synthesized using activators regenerated by electron transfer (ARGET) for atom transfer radical polymerization (ATRP). Polydispersity of the PMA block was varied by adjusting the amount of copper catalyst in ARGET ATRP, and the resulting molecular weight distributions were found to be approximately symmetric. At a composition of 35 vol % of PMA, the formation of a hexagonally perforated lamellar (HPL) morphology was observed for a polydisperse PS−PMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
128
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 52 publications
6
128
1
4
Order By: Relevance
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report. This topic recently has been reviewed, 44 and only a brief summary is provided below.…”
Section: Introductionmentioning
confidence: 93%
“…A flurry of theoretical [25][26][27][28][29][30][31][32][33][34] and a͒ Authors to whom correspondence should be addressed: Electronic addresses: hillmyer@umn.edu and bates@cems.umn.edu. experimental 11,27,[35][36][37][38][39][40][41][42][43] studies of polydispersity effects in AB block copolymers followed Bendejacq et al's report. This topic recently has been reviewed, 44 and only a brief summary is provided below.…”
Section: Introductionmentioning
confidence: 93%
“…Although long time the idea was set that ordered microphases in block copolymers can be achieved only by a narrow dispersity, [68] some studies have demonstrated their self-assembly into well-ordered structures even presenting a broader molecular weight distribution (MWD). [69][70][71][72][73] Our starting materials for the blends exhibit, with values of 1.16 and 1.19 for neat SIM and ISM, by themselves relatively broad MWDs and as both terpolymers have unequal molecular weights the combination in a blend provides both a polydispersity in molecular weight and composition. The repulsive segmental interactions between the copolymer blocks is the driving force for microphase separation and leads them to stretch in order to adopt a minimum of interfacial contact area.…”
Section: Resultsmentioning
confidence: 92%
“…Other solvent ratios produced mixed morphology structures such as comb-like patterns from coexisting At a composition of 35 vol% of poly(methyl acrilate) (PMA), the formation of a HPL morphology was observed for a polydisperse poly(styrene-b-methyl acrilate) (PS-b-PMA) copolymer for short-and long-term solvent-casting conditions [30], as it can be seen in Figure 7. The hexagonal arrangement of the PS perforations is clearly visible in the upper right inset of the Figure which depicts a plane view of the PMA layer.…”
Section: Perforated Lamellar Morphologymentioning
confidence: 96%
“…Even if in the bulk state, the perforated lamellar morphology of block copolymers has been reported to be a metastable state of the gyroid (G) phase, under thin film confinement conditions, one-dimensional confinement provides stability to the phase [26,27] and has been found for different diblock copolymer thin films under several conditions [26][27][28][29][30][31][32][33][34][35]. For thin films of poly(styrene-b-dimethylsiloxane) (PS-b-PDMS) diblock copolymer spin coated onto silicon wafers modified with hydroxyl-terminated PDMS subject to solvent vapor annealing, depending on the film thickness, its commensurability with the microdomain period, and the ratio of toluene/heptane vapors used for the solvent annealing process, perforated lamellae morphology can be obtained [26], besides spheres, cylinders, or gyroids.…”
Section: Perforated Lamellar Morphologymentioning
confidence: 99%